تقييم النتائج العلاجية لابيضاض النقوي المزمن إيجابي فيلاديلفيا باستخدام مركب Imatinib Mesylate (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث إلى دراسة فعالية مركب Imatinib Mesylate في علاج الابيضاض النقوي المزمن, ولاسيما فعاليته النقوية والبيولوجية فضلا عن الفعالية الدموية عند مرضى الابيضاض النقوي المزمن إيجابيي صبغي فيلاديلفيا. أعطيت المعالجة لـ 28 مريض أغلبهم من الشباب والراغبون بزرع نقي العظم بجرعة من 400 إلى 600 ملغ يومياً دفعةً واحدة، بعضهم خضع لعلاجات أخرى سابقة. تمت مراقبة المرضى في أثناء المعالجة بتقييم دموي شهري مع تقييم نقوي كل ثلاثة أشهر وتقييم بيولوجي كل ستة أشهر، فضلا عن المتابعة السريرية. تمت المعالجة بدون اختلاطات قاتلة وحصل تحسن دموي منذ الشهر الأول حتى هوادة دموية كاملة خلال ثلاثة أشهر عند 24 مريض أي 85.7% من المرضى. الهوادة الصبغية الكاملة (صبغي فيلاديلفيا أقل من 5%) شوهد عند 9 مرضى أي 32.14% بعد ستة أشهر و11 مريض بعد سنة أي 39.29% من المرضى. أما الهوادة الجزئية (صبغي فيلاديلفيا بين 6-35%). شوهد عند سبعة مرضى 25% بعد ستة أشهر وعند تسعة مرضى عند 32.14% بعد سنة من المعالجة. تراجع الطحال بمعدل 5-10 cm من قطره الطولي عند 16 مريض أي 57.14% من المرضى. لم تحدث أية وفاة بسبب المعالجة.   The research aims to study the efficacy of Imatinib Mesylate drug in treatment of CML, according to the hematomyelo, and biologic effect in patients with positive Philadelphia chromosome. Twenty eight patients were included in this study, most of them were young adults, and candidates for bone marrow transplantation, some of them had been previously treated with another treatment without success. The doses ranged between 400-600 mg once daily. Patients were evaluated before treatment, observed during treatment with monthly blood evaluation, myelocytic evaluation every three months, and biologic evaluation every six months, in addition to clinical follow up. Treatment was done without serious complications. Hematological improvement was observed at the end of the first month, with complete remission in 24 patients (85.7%) within 3 months. Complete chromosome remission (Ph-chromosome less than 5%) was seen in 9 patients (32.14%) after 6 months, and in 11 patients (39.29%) after one year .Partial remission (Philadelphia chromosome between 6-35%) was seen in 7 patients (25%) after 6 months and in 9 patients (32.14%) after 1 year of treatment. The spleen length decreased by 5-10 cm of original meridian in 16 patients (57.14%). No deaths had occurred because of the treatment.